PENGEMBANGAN WISATA KAMPUNG PELANGI MELALUI PEMBERDAYAAN MASYARAKAT DI KOTA SEMARANG - Cahyaningrum, Putri; Retno, Nunik (Journal of Politic and Government Studies, 2019)
Kampung Pelangi is one of the tourist destinations that are new and unique in the city of Semarang, Kampung Pelangi are well known by local and foreign tourists through various social media or other media. The purpose of this research is to know the process of community empowerment through the development of tourism, while the role of Government in developing Tours Kampong Pelangi. This research is descriptive research with qualitative approach, data collection is done using the techniques of observation, interviews, and documentation. The results showed that the process of community empowerment in Kampung Pelangi takes place in three stages, namely the stage of awareness, capacity building, and the granting of power to the importance of the role of Government in the development of Kampung Pelangi tourism the Government has three roles, namely Motivators, with form Pokdarwis to implement the socialization and guidance. Social monitoring via PokdarwisKeywords: Community Empowerment, Development Of Tourism, Kampung Pelangi